A Syntactic Analysis of Noun Phrase Structures in The Jakarta Post Editorials - Anjani, Juli; Ezir, Ely; Fitriani, Eka Surya; Panggabean, Edward Dolmer (JOURNAL OF LANGUAGE, 2026)
This research analyzes the syntactic structures of noun phrases found in the editorial section of The Jakarta Post newspaper. This study addresses the limited research on noun phrase structures in Indonesian English-language media. Using a qualitative descriptive method, the study examines noun phrases in three editorials published from June 3 to 5, 2024. The analysis identifies eight types of noun phrase structures: Determiner + Noun, Adjective + Noun, Determiner + Adjective + Noun, Determiner + Quantifier + Noun, Determiner + Participle + Noun, Noun + Prepositional Phrase, Noun + Adjective Phrase, and Noun + Relative Clause. The findings reveal that the most frequently used structure is Adjective + Noun (24.7%), followed closely by Determiner + Noun (24.0%). These results indicate a strong tendency in journalistic writing to employ descriptive language while maintaining specificity and clarity. The study also reveals that noun phrases in The Jakarta Post serve multiple functions including subjects, objects, and complements, with complex structures such as Noun + Prepositional Phrase (16.9%) and Determiner + Adjective + Noun (17.5%) being used to provide additional context and nuanced information. This research contributes to understanding how English syntax functions in Indonesian media contexts and offers insights for linguistics educators, students, and media professionals regarding the practical application of noun phrase structures in journalistic writing.